First-derivative ultraviolet spectrophotometric and high performance liquid chromatographic determination of ketoconazole in pharmaceutical emulsions (Revista Brasileira de Ciências Farmacêuticas, 2006)
First-derivative ultraviolet spectrophotometric (Method I) and reversed phase high performance liquid chromatographic (Method II) methods were developed. The validated methods were applied for quantitative determination of ketoconazole in commercial and simulated emulsion formulations. Quantitative first-derivative UV spectrophotometric determinations were made using the zero-crossing method at 257 nm, with methanol as background solvent. Liquid chromatographic analysis was carried out on a LiChrospher® 100 RP-18 (5µm) column. A mixture of triethylamine in methanol (1:500 v/v) and 0.5% ammonium acetate solution (75:25 v/v) was used as mobile phase at a flow rate of 1.0 mL/min with UV detection at 225 nm. The retention time of ketoconazole and terconazole were 3.9 min and 5.9 min, respectively, the later being used as internal standard. Analytical curves were linear within a concentration range from 5.0 to 30.0 µg/mL for Method I and 20.0 to 80.0 µg/mL for Method II, with correlation coefficients of 0.9997 and 0.9981, respectively. The relative standard deviation (RSD) was 0.56% and 0.41% for simulated and commercial emulsion formulations, respectively, using Method I. The corresponding values were 2.13% and 1.25%, respectively, using Method II. The percentage recoveries were above 100% for both methods. The excipients did not interfere in the analysis. The results showed that either method can be used for rapid ketoconazole determination in pharmaceutical emulsions with precision, accuracy and specificity.